Synthesis of Heterobiaryls Featuring 1,4 N···S Inter-Ring Interactions - Tilly, David; Chevallier, Floris; Mongin, Florence (Synthesis, 2016)
Because of its low-lying σ* orbitals, the C–S bond can interact with electron donors. In this short review, our goal is to focus on intramolecular interactions between bivalent sulfur and basic nitrogen atoms. In particular, we will consider the synthesis of selected heterobiaryls for which 1,4 N···S inter-ring interactions can be identified from X-ray diffraction data. Finally, we will briefly touch on the use of such conformational preferences in various applications. 1 Introduction 2 Cross-Coupling with C–C Bond Formation 3 Cross-Coupling with C–N Bond Formation 4 Nucleophilic Addition to Azine Followed by Oxidation 5 Multicomponent Reactions 6 Heterobiaryl Formation by Azine Building 7 Heterobiaryl Formation by Building of the Sulfur-Containing Heterocycle 8 Cycloaddition Reactions 9 Other Syntheses10 Conclusion
Keywords: heterobiaryls; nitrogen; sulfur; azines; heterocycles; cross-coupling; X-ray diffraction